Evaluation of satellite and reanalysis‐based global net surface energy flux and uncertainty estimates. Issue 12 (26th June 2017) - Liu, Chunlei; Allan, Richard P.; Mayer, Michael; Hyder, Patrick; Loeb, Norman G.; Roberts, Chris D.; Valdivieso, Maria; Edwards, John M.; Vidale, Pier‐Luigi
Abstract: The net surface energy flux is central to the climate system yet observational limitations lead to substantial uncertainty. A combination of satellite‐derived radiative fluxes at the top of atmosphere adjusted using the latest estimation of the net heat uptake of the Earth system, and the atmospheric energy tendencies and transports from the ERA‐Interim reanalysis are used to estimate surface energy flux globally. To consider snowmelt and improve regional realism, land surface fluxes are adjusted through a simple energy balance approach at each grid point. This energy adjustment is redistributed over the oceans to ensure energy conservation and maintain realistic global ocean heat uptake, using a weighting function to avoid meridional discontinuities. Calculated surface energy fluxes are evaluated through comparison to ocean reanalyses. Derived turbulent energy flux variability is compared with the Objectively Analyzed air‐sea Fluxes (OAFLUX) product, and inferred meridional energy transports in the global ocean and the Atlantic are also evaluated using observations. Uncertainties in surface fluxes are investigated using a variety of approaches including comparison with a range of atmospheric reanalysis products. Decadal changes in the global mean and the interhemispheric energy imbalances are quantified, and present day cross‐equator heat transports are reevaluated at 0.22 ± 0.15 PW (petawatts) southward by the atmosphere and 0.32 ± 0.16 PW northward by the ocean considering the observed ocean heat sinks. Key Points: Improved global net surface energy flux estimates by combining satellite and atmospheric reanalysis data Zonal multiannual mean standard deviation across five reanalysis surface flux estimates (11 Wm −2 ) reduced to 2.6 Wm −2 using new method Cross‐equator heat transport reevaluated: 0.22 PW to south by atmosphere and 0.32 PW to north by ocean